Evolution of the thyroid hormone-binding protein, transthyretin - Power, Deborah (2000)
Transthyretin (TTR) belongs to a group of proteins, which includes thyroxine-binding globulin and albumin, that bind to and transport thyroid hormones in the blood. TTR is also indirectly implicated in the carriage of vitamin A through the mediation of retinol-binding protein (RBP). It was first identified in 1942 in human serum and cerebrospinal fluid and was formerly called prealbumin for its ability to migrate faster than serum albumin on electrophoresis of whole plasma.